Investigation of antennas and energy harvesting methods for use with a UHF microtransceiver in a biosensor network - Hodges, Amelia Lynn (Kansas State University, 2013)
This work was a part of NASA EPSCoR Project NNX11AM05A: Biosensor Networks and Telecommunication Subsystems for Long Duration Missions, EVA Suits, and Robotic Precursor Scout Missions. The project’s main goal is the development of a wireless sensor network inside an astronaut’s spacesuit. Antennas are essential components in a wireless network. Since this antenna will be used inside the spacesuit it is important to consider both the physical size limitations and the desired antenna polarization. After exploring the WWVB radio station antenna which provides the preferred vertical polarization and has a suitable aspect ratio, the top hat antenna seemed promising for intrasuit communication. The design of a top hat antenna is outlined. Then, the antennas were tested using 433 MHz radios in a full scale model spacesuit. This spacesuit was designed specifically to model the behavior of aluminized mylar in the real suit. Test results support the feasibility of an intrasuit wireless network. If a gateway radio is placed on the chest or back, a sensor could be placed anywhere on the body and provide an adequate signal. These initial tests did not include a matching network, but the additional link-margin afforded by a matching network, even an imperfect match, is considered. Energy harvesting is explored as an alternative to batteries powering the intrasuit radio. In the oxygen rich environment of a spacesuit, even the smallest spark can be catastrophic. A variety of energy harvesting options are explored with a focus on thermal energy harvesting. The temperature difference between the human skin and the astronaut’s Liquid Cooling and Ventilation Garment can be used to produce a small voltage. To increase the voltage a step-up converter is implemented. Final integration of the two systems with a biosensor is left for on-going work in the three year NASA project.
Keywords: Top hat antenna; Antenna testing; Thermoelectric Generators; Energy harvesting; Electrical Engineering (0544)